Stenting as a bridge to surgery for obstructed stage IV colorectal cancers – long‐term outcomes of a 10‐year study. Issue 3 (22nd August 2019) - Chok, Aik Yong; Lim, Hui Jun; Lye, Weng Kit; Samarakoon, Lasitha B; Guo, Jiwei; Tang, Choong Leong; Mathew, Ronnie
Abstract: Introduction: Successful stenting of an obstructing colorectal tumor can avert upfront emergency surgery in malnourished obstructed patients with metastatic disease and poor physiological condition. This study aims to evaluate the outcomes of stenting followed by primary colorectal tumor resection among patients with obstructed stage IV colorectal cancer at presentation, over a 10‐year period. Methods: From 2007 to 2016, a cohort comprising 25 consecutive patients were retrospectively reviewed from a prospectively collected database. The durability of palliation of bowel obstruction, oncological outcomes and factors influencing overall survival were analyzed. Results: No re‐interventions were required for bowel obstruction during the study period. The overall perioperative morbidity rate was 16%, with no postoperative 90‐day mortality. Laparoscopic resection rate was 52% and stoma formation rate was 8%. The median overall survival was 24 months for the entire cohort, and the 1‐, 3‐ and 5‐year survival rates were 80%, 35% and 23.33% respectively. More than one site of distant metastases, peritoneal involvement, and elevated carcinoembryonic antigen levels were significantly associated with poorer survival outcomes. Patients with peritoneal‐only metastasis had worse outcomes, with a median survival of 7 months and no patients surviving beyond 18 months. Conclusion: Stenting followed by resection of the primary obstructing colorectal cancer provides durable palliation among patients with stage IV disease, with low perioperative morbidity and stoma formation rates. Superior survival was observed among patients with single‐site, non‐peritoneal distant metastases.